2015
DOI: 10.1155/2015/763919
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of Chinese Doppler Radar and Lightning Data Using WRF-GSI: A Case Study of Mesoscale Convective System

Abstract: The radar-enhanced GSI (version 3.1) system and the WRF-ARW (version 3.4.1) model were modified to assimilate radar/lightning-proxy reflectivity. First, cloud-to-ground lightning data were converted to reflectivity using a simple assumed relationship between flash density and reflectivity. Next, the reflectivity was used in the cloud analysis of GSI to adjust the cloud/hydrometeors and moisture. Additionally, the radar/lightning-proxy reflectivity was simultaneously converted to a 3D temperature tendency. Fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 41 publications
0
18
0
1
Order By: Relevance
“…Therefore, the FY-4A lightning data lacks a detailed comparative evaluation with lightning data detected by other satellites in this study. It is necessary to conduct a more detailed assessment of the FY-4A LMI lightning data in the future [33]. Besides, in this lightning data assimilation method, a wet bias might be created or increased to cause the spurious severe convection produced, which indicates the lightning assimilation method could combine with other methods to adjust the hydrometeors towards smaller values at spurious regions to limit spurious convection effectively [19,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the FY-4A lightning data lacks a detailed comparative evaluation with lightning data detected by other satellites in this study. It is necessary to conduct a more detailed assessment of the FY-4A LMI lightning data in the future [33]. Besides, in this lightning data assimilation method, a wet bias might be created or increased to cause the spurious severe convection produced, which indicates the lightning assimilation method could combine with other methods to adjust the hydrometeors towards smaller values at spurious regions to limit spurious convection effectively [19,51].…”
Section: Discussionmentioning
confidence: 99%
“…Some other researchers converted lightning data into proxy radar reflectivity and then assimilated the proxy reflectivity [27][28][29][30][31][32]. This scheme has been evaluated via different assimilation methods (DDFI [33]; EnKF [16]) in DA systems, and the results demonstrated that it can improve the accuracy of reflectivity prediction as well as short-term rainfall forecasts, especially in areas with missing radar data [34].…”
Section: Introductionmentioning
confidence: 99%
“…However, each method had shortcomings; for example, cloud analysis provided stronger precipitation in short-term forecasts after assimilation than was observed [33]. The physical initialization method provided a better precipitation forecast, but the improvement was short-lived [32].…”
Section: Introductionmentioning
confidence: 98%
“…In our previous work, we attempted to assimilate lightning data utilizing radar proxy reflectivity transformed in Gridpoint Statistical Interpolation (GSI) code using diverse methods such as physical initialization and cloud analysis [32][33][34]. However, each method had shortcomings; for example, cloud analysis provided stronger precipitation in short-term forecasts after assimilation than was observed [33].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we assimilated the cloud-to-ground or total flash rate into WRF via various methods. The cloud-to-ground flash rates were converted into proxy radar reflectivity basing on an empirical relationship in GSI (Girdpoint Statistics Interpolation) code, and then assimilated into the WRF model by physical initialization [28], WRF-GSI cloud analysis [29] and ensemble square root filter [30]. Total flash rates were converted into the proxy of relative humidity based on the relationship promoted by Fierro et al [26] and then assimilated via three-dimensional variational (3DVar) [31].…”
Section: Introductionmentioning
confidence: 99%